2008
DOI: 10.1016/j.drugalcdep.2008.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Drinkers and bettors: Investigating the complementarity of alcohol consumption and problem gambling

Abstract: Regulated gambling is a multi-billion dollar industry in the United States with greater than 100 percent increases in revenue over the past decade. Along with this rise in gambling popularity and gaming options comes an increased risk of addiction and the associated social costs. This paper focuses on the effect of alcohol use on gambling-related problems. Variables correlated with both alcohol use and gambling may be difficult to observe, and the inability to include these items in empirical models may bias c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 57 publications
(61 reference statements)
2
33
0
5
Order By: Relevance
“…Welte et al, 2001; Welte et al, 2014), nonetheless, 73% of the pathological gamblers had an alcohol disorder, 38% had a drug use disorder, and 60.4% had nicotine dependence (Petry et al, 2005). Also analyzing the NESARC data, French, Maclean and Ettner (2008) found that alcohol consumption was positively associated with the likelihood of experiencing any gambling-related problems and with the number of problems experienced, taking into account geographic areas with more alcohol sales. Chou and Afifi (2011) used two waves of NESARC data and demonstrated a significant effect of disordered gambling (problem and pathological gambling together) on alcohol dependence after adjusting for demographic factors and other medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Welte et al, 2001; Welte et al, 2014), nonetheless, 73% of the pathological gamblers had an alcohol disorder, 38% had a drug use disorder, and 60.4% had nicotine dependence (Petry et al, 2005). Also analyzing the NESARC data, French, Maclean and Ettner (2008) found that alcohol consumption was positively associated with the likelihood of experiencing any gambling-related problems and with the number of problems experienced, taking into account geographic areas with more alcohol sales. Chou and Afifi (2011) used two waves of NESARC data and demonstrated a significant effect of disordered gambling (problem and pathological gambling together) on alcohol dependence after adjusting for demographic factors and other medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also found high rates of alcohol abuse and alcoholism among pathological gamblers (French, Maclean & Ettner, 2008;Stewart & Kushner, 2005). The studies carried out to date show rates ranging from 11% to 70%, with wide variability among studies (Bland et al, 1993;Kausch, 2003;Martínez-Pina et al, 1991;Ramírez, McCormick, Russo & Taber, 1983;Specker, Carlson, Edmonson, Johnson & Marcotte, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Plus un joueur dépense d'argent en stupéfi ants par mois et moins il est probable qu'il cesse de jouer aux jeux de hasard et d'argent durant ce mois (Odds Ratio = 0,308 ; p ≤ 0,01 ; à chaque valeur additionnelle du logarithme des dépenses en intoxiquant les probabilités de ne pas s'abstenir augmentent de 3,25 fois). Ce résultat corrobore d'une certaine manière l'argument voulant que le jeu problématique et la consommation de stupéfi ants soient en fait des activités complémentaires (French et al, 2008) ou la thèse selon laquelle la consommation d'alcool ou de substances psychoactives favorise la surenchère des mises jouées (Chesher et Greeley, 1989). Les prêts usuraires exercent le même effet de maintien des habitudes de jeu : les mois où les joueurs remboursent un tel prêt viennent en quelque sorte miner les chances que le jeu s'interrompe (Odds Ratio = 0,363 ; p ≤ 0,01).…”
Section: L'abstinence Au Jeuunclassified